ZnO nanostructures synthesized by one-step sol-gel process using different zinc precursors - Maneerat Songpanit; Kanokthip Boonyarattanakalin; Wisanu Pecharapa; W Mekprasart (Journal of Metals Materials and Minerals, 2024)
Zinc oxide (ZnO) nanopowders have been widely applied in electronics, optics and photocatalytic applications depending on their morphological structure. In the bottom-up process, it is conceived that the different zinc precursors may result in different formations of ZnO nanostructures with exceptional morphology. This work focuses on ZnO material synthesized via the facile sol-gel synthesis using different zinc slat precursors, including zinc acetate, zinc nitrate, zinc sulphate, and zinc chloride. All zinc salt precursors were incorporated with sodium hydroxide and hexamethylenetetramine (HMTA) under mild thermal energy with consistent conditions to investigate ZnO formation. The as-prepared samples appeared in white powders with different aggregation features. The crystalline phase, surface morphologies, and element mapping of all ZnO samples were analyzed using X-ray diffraction technique (XRD) and field emission scanning electron microscope (FE-SEM). The chemical bonding structure of ZnO powders was characterized by Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy. The specific surface area per volume of ZnO nanopowders obtained by different zinc salt precursors was analyzed by Brunauer-Emmett-Teller (BET) method. All ZnO samples obtained from various zinc salt precursors exhibited a high crystallinity of the wurtzite structure without other impurities. The structural properties of ZnO nanopowders demonstrated different sizes and structures with distinguished formation and aggregation depending on the zinc precursor basic strength being used.
Keywords: ZnO doping and properties; Gas Sensing Nanomaterials and Sensors; Copper-based nanomaterials and applications